Cosmopolitan Morality: A Critical Review of Peter Singer’s Ethics in the Real World and Its Implications for Public Policy - Pratama, Obi (Abjad Journal of Humanities & Education, 2025)
Ethical reasoning must traverse national and epistemic boundaries in an era of transboundary pandemic s and planetary crises. This article assesses Peter Singer's Ethics in the Real World, a collection of eighty-two essays articulating a stringent utilitarian call to minimize suffering through impartial and cost-effective intervention. Drawing on the cosmopolitan frameworks of Appiah, Nussbaum, and Sen, the review explores Singer's four thematic clusters—animal ethics, effective altruism, bioethics, and climate responsibility—while critiquing their translatability into the cultural and institutional landscapes of the Global South. Case studies from Indonesia, Rwanda, and Kenya demonstrate how communitarian reciprocity, religious obligation, and postcolonial memory complicate universalist prescriptions. Framed within normative international ethics, the article engages Singer's proposals as moral philosophy and implicit theory of cross-border responsibility. It further suggests two forward-looking strategies: embedding participatory deliberation in ethical policy frameworks and integrating comparative ethics into administrative training. Ultimately, the article contributes to interdisciplinary debates at the intersection of philosophy, development ethics, international relations, and public governance—where universal principles must be continually renegotiated through plural voices in shared reasoning.